2012
DOI: 10.1172/jci61014
|View full text |Cite
|
Sign up to set email alerts
|

Partial MCM4 deficiency in patients with growth retardation, adrenal insufficiency, and natural killer cell deficiency

Abstract: Natural killer (NK) cells are circulating cytotoxic lymphocytes that exert potent and nonredundant antiviral activity and antitumoral activity in the mouse; however, their function in host defense in humans remains unclear. Here, we investigated 6 related patients with autosomal recessive growth retardation, adrenal insufficiency, and a selective NK cell deficiency characterized by a lack of the CD56 dim NK subset. Using linkage analysis and fine mapping, we identified the disease-causing gene, MCM4, which enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
292
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(307 citation statements)
references
References 57 publications
14
292
0
1
Order By: Relevance
“…29 In humans, a recessive condition called Meier-Gorlin syndrome, which is caused by an N-terminal truncation of MCM4 leads to increased chromosomal fragility in patients' lymphocytes and dermal fibroblasts. 30,31 A similar phenotype of DNA breaks and gaps was also observed in human aneuploid cell lines. Indeed, we demonstrated that the low levels of MCM2-7 are responsible for the replication defects in aneuploids, as restoring near wild-type levels of MCM2-7 partially alleviated the phenotype.…”
Section: Mechanisms Leading To Genomic Instabilitysupporting
confidence: 65%
“…29 In humans, a recessive condition called Meier-Gorlin syndrome, which is caused by an N-terminal truncation of MCM4 leads to increased chromosomal fragility in patients' lymphocytes and dermal fibroblasts. 30,31 A similar phenotype of DNA breaks and gaps was also observed in human aneuploid cell lines. Indeed, we demonstrated that the low levels of MCM2-7 are responsible for the replication defects in aneuploids, as restoring near wild-type levels of MCM2-7 partially alleviated the phenotype.…”
Section: Mechanisms Leading To Genomic Instabilitysupporting
confidence: 65%
“…Moreover, a selective view on CD56, CD16, and CD56 bright subsets is also helpful for the diagnosis of patients with defects in the NK-cell system, including those with mutations in the MCM4 gene. In MCM4 deficiency, it has been shown that patient's NK cells feature a lower CD16 expression, a selective loss of the CD56 dim subset and a higher CD56 bright / CD56 dim ratio (62). Classically, a clinical diagnosis in chronic immunodeficiencies is preceded by a specific clinical suspicion and subsequent diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…50) or MCM4 (REF. 51), lead to higher rates of malignancy. These primary immunodeficiencies affecting NK cells indicate how important these cells are in tumour immune surveillance.…”
Section: Nk Cell Functionsmentioning
confidence: 99%